2016
DOI: 10.1001/jamapediatrics.2016.2132
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Antibiotic Use and Neonatal Mortality and Morbidities in Very Low-Birth-Weight Infants Without Culture-Proven Sepsis or Necrotizing Enterocolitis

Abstract: IMPORTANCE Excessive antibiotic use has been associated with altered bacterial colonization and may result in antibiotic resistance, fungemia, necrotizing enterocolitis (NEC), and mortality. Exploring the association between antibiotic exposure and neonatal outcomes other than infection-related morbidities may provide insight on the importance of rational antibiotic use, especially in the setting of culture-negative neonatal sepsis. OBJECTIVE To evaluate the trend of antibiotic use among all hospitalized very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
147
1
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(165 citation statements)
references
References 42 publications
0
147
1
11
Order By: Relevance
“…Overall, the evidence reveals that although surgical case volume and illness severity might sometimes drive the AUR, a relatively high AUR also may be used to independently predict mortality and average length of stay. In a recent report, the Canadian Neonatal Network found that higher AURs were associated with adverse neonatal outcomes among infants without culture-proven sepsis or NEC, including a twofold increase in mortality odds associated with a 10% AUR increase 20 . A possible contributing factor is dysbiosis associated with neonatal antibiotic exposure 21 ,.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the evidence reveals that although surgical case volume and illness severity might sometimes drive the AUR, a relatively high AUR also may be used to independently predict mortality and average length of stay. In a recent report, the Canadian Neonatal Network found that higher AURs were associated with adverse neonatal outcomes among infants without culture-proven sepsis or NEC, including a twofold increase in mortality odds associated with a 10% AUR increase 20 . A possible contributing factor is dysbiosis associated with neonatal antibiotic exposure 21 ,.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse neonatal outcomes are increased in very-low-birthweight infants treated with antibiotics that did not have culture-proven sepsis [21]. While in adults, all-cause mortality, appropriate therapy and shorter mean duration of therapy was improved in surgical ICU patients that followed conservative antimicrobial treatment as compared to aggressive antimicrobial administration [22, 23].…”
Section: Improved Patient Management Versus 30+ Years Of Therapeutic mentioning
confidence: 99%
“…We do not think that prolonged perioperative prophylaxis will reduce the rate of bacterial infection complications, but might pose other risks to the patient such as selection of multi‐resistant bacteria, increasing the risk for invasive candidiasis or changes of the microbiome. Indeed, there is a growing body of evidence that prolonged or unnecessary antibiotic therapy leads to a worse outcome in different patient populations . Nevertheless, for pediatric liver transplant patients, neither short nor long perioperative prophylaxis has been proven to be superior.…”
Section: Discussionmentioning
confidence: 99%